Quando as luzes não se apagam... a gestão coletiva dos riscos na manutenção em rede energizada - Marcelle La Guardia Lara de Castro (2016)
With the reduction of its own workforce, an electric company came up with an alternative in order to adapt the teams that work with the maintenance of Medium Voltage (MV) electric power aerial distribution: introducing a new work organization with the pairs. Until then, these Hot Line (HL) teams have three members; but a study undertaken by the companys engineering, training sector and electricians pointed out the viability of performing the work with two members. On one side, these actors claim that it is technically possible to do it; and, on the other, electricians and unions claim that working in pairs will affect the health and safety of the workers on the HL. This research was aimed at investigating the elements at stake about the (im)possibilities of the pairs, starting from the arguments of the HLs electricians and from the arguments of the managers and technicians about this new model of organization, thus placing the electricians activity in the core of the analysis. An action research was proposed in order to take the first steps into an investigation based upon real work conditions. The Action Research, the Grounded Theory (GT) and the Ergonomics Workplace Analysis (EWA) were mobilized as methodological and theoretical support. Semi-structured interviews, general and systematical observations, self-confrontations and validation groups were conducted, in which technicians and electricians of two different units of the company took part. The main safety conditions for the work in pairs identified were: to assure the physical and mental ability of the team by performing only the jobs classified as light by the field workers themselves, by work relays so that the conditions for supervision and performance arent affected; to take into consideration the electricians age and its physical impact on the job performance when forming the teams; to develop competences in a way that englobes the tacit and implicit knowledges in the living with the team (which brings into question whether two years are enough); to provide the necessary conditions for the organization, maintenance and development of the collective, which are compatible with the cognitive and emotional requirements of the jobs content; to define the complexity so that the dynamic elements of the situation can be reached in interaction with the team (not only of the job or the performer on its own); in the union between the teams, to ensure that the mentioned elements of trust will be present. Thus, it is shown how the construction of a work safety that incorporates the workers savoir-faire advances beyond the preventive actions that aim at the application of general technical-scientific knowledges, by integrating the microscopic dimension of the situations at work with their singularity. Finally, we evaluate to what extent these conditions are satisfied in the real situations of intervention, bringing operational and economic viability criteria for the work in pairs